Maintenance and Philosophy of Technology (Taylor & Francis, 2024)
What can we learn about the nature of technology by studying practices of maintenance and repair? This volume addresses this question by bringing together scholarship from philosophers of technology working at the forefront of this emerging and exciting topic. The chapters in this volume explore how attending to maintenance and repair can challenge and complement existing ways of thinking about technology focused on use and design and introduce new philosophical perspectives on the relationship between technology, time and human practice. They examine the significance of maintenance and repair practices at different scales in relation to a diverse range of philosophical traditions and a wide variety of technologies, from urban infrastructure such as bridges and buildings to data technologies such as servers and software systems. Together, the contributions highlight common themes in the philosophical study of maintenance, including the role of skill, the significance of social values and the potential of these practices to transform the technologies to which they are applied. By reflecting on the different ways in which we keep technologies going, from the devices we use in our homes to the large technical systems which surround us, this volume reveals the philosophical significance of practices of maintenance, not only as a source of new insights but also as a resource for enriching our understanding of a variety of existing topics in philosophy. Maintenance and Philosophy of Technolog will appeal to scholars and advanced students working in philosophy of technology, philosophy of engineering and science & technology studies.